Immunohistochemical expression of Cyclin D1 and p53 in normal, hyperplastic and malignant endometrium in a rural tertiary care hospital of central India: Expression of Cyclin D1 and p53 - Fulzale, Neha; Atram, Manisha; Shivkumar, Vitaladeuni (Chronic Diseases Journal, 2025)
BACKGROUND: Endometrial carcinoma (EC) is the most common gynecological malignancy worldwide. Type I EC is often preceded by atypical endometrial hyperplasia (EH), while type II EC results from a series of genetic alterations involving activation of proto-oncogene (cyclin D1) and inactivation of tumor suppressor genes (p53). The purpose of this study was to evaluate prognostic significance of cyclic D1 and p53 expression in cases of EC by immunohistochemistry (IHC). METHODS: This laboratory-based observational study was conducted in the histopathology section of the Department of Pathology at a rural tertiary care hospital in Central India from 2017 to 2019. The study comprised 100 cases, of which 50 cases were of EC and 38 and 12 cases of EH and normal endometrium, respectively. Relevant clinical details, histopathological diagnosis, treatment, and follow-up were retrieved from the Hospital Information System (HIS) and pathology records. IHC evaluation of cyclin D1 and p53 was done in all cases. Statistical analysis was done by descriptive and inferential statistics using a chi-square test through SPSS software. RESULTS: Cyclin D1 was significantly over-expressed in atypical EH and type I EC. Overall, the positivity of cyclin D1 in EC was 88%. The high expression of cyclin D1 was significantly associated with poorly-differentiated tumors (P = 0.023). Overexpression of p53 was strongly associated with type II histology and poorly-differentiated type I EC, the presence of lymphovascular invasion (LVI) (P = 0.059), and advanced International Federation of Gynecology and Obstetrics (FIGO) stage (P = 0.0011). CONCLUSION: Cyclin D1 expression increased from normal endometrium to hyperplasia and EC, thus suggesting its role in the pathogenesis of type I EC, while p53 overexpression was significantly higher in type II EC and poorly-differentiated EC. Therefore, cyclin D1 and p53 can be used as a marker for endometrial carcinogenesis and tumor cell proliferation.